Essentials of biology - Janet L Hopson (McGraw-Hill, 1990)
This book is divided into six parts: 1) The first part discusses the building blocks of all matter; biological molecules, the stuffs of cells and organisms; the flow of energy in living things; the parts of cells and how they function; and the central energy pathways of cellular respiration and photosynthesis. 2) The second part covers cellular reproduction, the mechanisms of heredity, and how genes and chromosomes control the daily functions of living cells. 3) The thisd part presents a clear picture of the wide spectrum of organisms and their basic characteristics. 4) The fourth and fifth parts describe the phisiology of the plants and animals, and how they interact with their environments. 5) The final part introduces the science of evolution and ecology